COVID-19 in artisanal and small-scale mining communities: Preliminary results from a global rapid data collection exercise. Issue 121 (July 2021) - Perks, Rachel; Schneck, Nathan
Highlights: Rapid global data collection exercise in artisanal mining communities to examine impacts of COVID-19. 22 countries covered. 20 data collection partners. Over 2000 persons surveyed. Abstract: As early as March 2020, anecdotal reports and some news stories began trickling in about COVID-19 related restrictions and their impacts on strategic mineral supply chains, and the miners who labor in the informal mining sector. However, these reports were few and far between. Imperative was the need for a more accurate and comprehensive picture of the situation, should development partners wish to respond rapidly and accurately to the possible crisis developing in artisanal and small-scale mining (ASM). The World Bank, along with a range of development partners, 1 set out to understand how COVID-19 is influencing the development trajectories of select ASM communities (Delve, 2020a ). By way of a standardized short questionnaire administered by telephone, researchers conducted rapid surveys on a bi-weekly basis with miners in ASM communities spread across 22 countries (Delve, 2020a ) and mining a total of nine minerals. 2 The questionnaire contained seven main areas of inquiry: (i) knowledge on COVID-19 and its prevention; (ii) access to work; (iii) food security; (iv) human security; (v) service delivery; (vi) supply chains; and (vii) recovery perspectives. More than 3400 responses were gathered over the full data collection period, providing rich snapshots of the impacts being felt by mining communities. The results, as discussed in this viewpoint piece, suggest that whilst ASM continues to offer important livelihoods, even amidst crisis such as COVID-19, the sector is yet to be fully integrated into sustainable development discussions. Formalization, a broad term to capture efforts to strengthen the legitimacy of ASM, is at a critical juncture where the disruption brought about by the global pandemic could yield new, vibrant and promising measures to further support the growth and sustainability of this important global productive sector.